Cellulosic ethanol from rice straw - Magallanes, Juniper V., et al (SOTECH, UPVisayas, 2012)
Due to the increasing demand for biofuels and the abundance of raw material in the country, the concept of cellulosic ethanol plant using rice straw was conceptualized.